OCCUPATIONAL THERAPY PRACTITIONER'S GUIDE TO SCHOOL-BASED PRACTICE - Dokken, Karel L.; Luna, John S.; Still, Susan E. ([S.l.] : ROUTLEDGE, 2024)
Using a practical, nuts and bolts' approach to school-based occupational therapy services, this unique text guides both entry level and experienced practitioners through the evaluation, intervention, and dismissal process in an educational setting. Beginning with an overview of the purpose of school-based interventions, the authors map out current populations, programs, and legal and licensing standards to give school-based practitioners the knowledge to practice safely and ethically. The book then explores how to successfully navigate the referral process from eligibility to intervention, incorporating helpful tips and references to help establish patterns of best practice. It also features numerous examples of current and reliable evaluations so that practitioners can expand their repertoire of assessments while ensuring a holistic avenue of care to reflect the distinct value of occupational therapy. Written by authors with a wealth of experience in this field, the book will be essential reading for both new and more experienced occupational therapy practitioners, as well as students training towards working in a school-based context.
Keywords: Occupational therapy; MEDICAL / Allied Health Services / Occupational Therapy